Cold plasma studies on the influence of surface microstructured thickness in the secondary electron emission from tungsten coatings. (March 2023) - de Castro, A.; Oyarzábal, E.; Tabarés, F.L.
Highlights: Pioneer studies on SEE dependence with tungsten microstructuring have been conducted in cold (glow discharge) helium plasmas. The presence of a 2500 nm thick microstructured tungsten surface decreases the SEE yield (respect to cold rolled) up to a factor 40 % at electron mean energies of 100–175 eV. Conversely, 500 nm coatings do not reduce the SEE yield even showing an increase at 25–100 eV. The SEE yields seems to be more influenced by the coating thickness rather than other questions derived by the differences in surface topology/pattern. Abstract: The Secondary Electron Emission (SEE) from the Plasma Facing Components, (PFCs) affects the plasma sheath and edge structure of magnetically confined toroidal plasmas with effects on the Scrappe Off Layer (SOL), heat transport and incident plasma heat flux to the divertor targets. It is also behind the performance degradation in aerospace devices as Hall thrusters. In future reactor prototypes using tungsten (W) components, much more demanding and longer term conditions for the exposed PFCs are expected. These scenarios will exacerbate the material degradation of the exposed surfaces that will change its morphology, thus modifying its plasma material interaction behavior. In such scenario, specific studies on the influence of the microstructure in the tungsten SEE yields become necessary. In these laboratory experiments, the SEE emission of different microstructured tungsten coatings exposed to helium Glow Discharge (GD) plasmas has been analyzed by using a previously developed laboratory technique. It enables the characterization of the I-V characteristics of the biased sample and, at the same time, the acquisition of the electron incident flux by using a gridded probe adjacent to the exposed sample. Different microstructured W coated samples differing in coating thickness (2500 nm and 500 nm) and primal substrate surface finishing (translated in final differences within the W coating topologies) were analyzed, also including cold rolled tungsten and original stainless steel (SS) substrate (material in which the microstructured tungsten film was deposited) as benchmarks for comparison. The overall results have shown that the presence of a 2500 nm thick microstructured W coating decreases the SEE yield of tungsten (cold rolled) up to a factor 40 % at electron mean energies of 100–175 eV. Conversely, 500 nm coatings did not reduce the SEE yield even showing an increase at 25–100 eV. The final increase/decrease in the obtained SEE yields seems to be more influenced by the microstructured coating thickness (where the role of intrinsic differences in oxygen content of the surfaces is discussed) rather than other questions possibly derived by the differences in surface topology (ordering, directionality and/or roughness of the microstructure features).